Association of Waist and Hip Ratio with the Angiographicc Severity of Coronary Artery Disease in Patients with Non ST Segment Elevation Myocardial Infarction - Noor Din, Muhammad Adeel, Rahidullah, Ejaz Ul Haq, Abdul Latif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Coronary artery disease and obesity cardiomyopathy, and cardiac autonomic neuropathy are the most prevalent types of cardiac involvement in the comorbid. Obesity has a two- to fourfold greater risk of developing coronary artery disease. Stroke and other cerebrovascular occurrences fare poorly for those with obesity and diabetes. Hospital, autopsy, epidemiological, longitudinal research, and other studies have all demonstrated the increasing prevalence of cardiomyopathy in diabetes and obese individuals Objective: the objective of the study is to association of waist and hip ratio with the angiographic severity of coronary artery disease in patients with non-ST segment elevation myocardial infarction Study Design: Cross sectional observational study Study Setting: This study was conducted in the department of Interventional Cardiology, National Institute of Cardiovascular Diseases (NICVD), Karachi from Ist August 2022 to 31st January 2023. Methodology: Total 120 subjects were enrolled in the study and divided in to two groups. Group I consisted of 60 patients with normal WHR, and group II consisted of 60 patients with elevated WHR. The history and anthropometric measurements were noted using a pre-designed structured form, including demographic data and a profile of potential risk factors. Three universal criteria for diagnosing myocardial infarction were used to confirm the presence of non-ST segment elevation myocardial infarction. Each participant’s signed permission was obtained before any data was collected. The patient’s waist and hip circumferences were measured the day before the CAG. At least two cardiologists engaged per patient’s therapy or the clinical context while evaluating the angiogram results. Visual estimation (in at least two orthogonal views) was used to estimate the vessel and Gensini scores to determine the degree of coronary artery disease on angiograms. The statistical analysis was done by using SPSS version 20. Results: Patients in Group II had a considerably higher mean body mass index and anthropometric status than those in Group I. The average WHR of the participants in the study is listed in order of increasing vascular involvement. For those with normal angiogram results, the average WHR was 0.98. There was a statistically significant difference (p<0.01) in the mean WHRs of those with single-vessel disease and the value of mean is gradually increased in scoring 1, 2 and 3. The WHR positively correlated with the severity of CAD as measured by vessel score (r=0.45). In addition, a positive connection (r=0.63) between WHR and CAD severity, as measured by the Gensini score. Multivariate logistic regression analysis of odds ratio (OR) for subject characteristics likely to cause coronary artery disease severity. Practical implication: In addition, there is only one local study, which provides scant information, and worldwide data is scant and conflicting about the relationship of the ratio of waist to hip with severe coronary artery disease (CAD). The incidence of obesity and coronary artery disease in Pakistan is much higher than in Western countries; thus, this study will offer more information regarding the relationship based on local data. Conclusion: The current study found that in individuals with non-ST-segment elevation myocardial infarction, increasing WHR was substantially correlated with the angiographic severity of coronary artery disease Keyword: WHR, BMI, Waist circumference, Cardiovascular disease